Impact of Poor Maintenance Work of Air-Conditioning in UTHM Lecture Hall Towards the User Comfort - Hisham, Mohammad Fateh; Omar, Roshartini; Mohamed, Sulzakimin; Md. Gharip, Nor Hazlin; Ismayatim, Norddin (Research in Management of Technology and Business, 2024)
Air conditioning has become indispensable, especially in warm climate to ensuring thermal comfort in various settings. Poor air conditioning system maintenance in university buildings can have a bad impact on the user comfort. Therefore, the research objectives of this study are to identify the issues faced by users related to maintenance work of air-conditioning at Universiti Tun Hussein Onn Malaysia (UTHM) lecture hall, to identify the impact of poor maintenance work of air-conditioning towards the user comfort and to suggest the ways of maintaining air-conditioning to give comfort to the user of the building. This study implemented quantitative method, where a questionnaire survey was distributed to the Faculty of Technology Management and Business, UTHM students. The data was collected from 215 respondents, which represents a 100% response rate. The data analysis method used was descriptive analysis by using Statistical Package for Social Science (SPSS) software. Study findings reveal that inefficient learning, productivity loss, and class availability issues are predominant challenges stemming from poor air conditioning maintenance. Additionally, health problems, poor exam results, and noxious odors emerge as adverse consequences. The research advocates environmental initiatives, regular filter replacement, and sealing/insulation as effective strategies for air conditioning maintenance. Ultimately, this study offers insights to enhance UTHM’s facility maintenance, aiming to create a conducive environment for users by addressing critical issues and implementing proactive measures.